Effectiveness of Entrepreneurship Practices to Foster the Interest of Entrepreneurship in SMK Muhammadiyah 1 Cilacap - Ulfa Hamadah; Tri Kuat (Universitas Ahmad Dahlan, 2022)
The objective of this study is to determine the effectiveness of entrepreneurial practices to foster the interest in entrepreneurship in Muhammadiyah 1 Vocational School of Cilacap. The research approach used by the researcher in the qualitative description. Data subjects came from students, resource persons, and teachers. Data collection techniques used by the researcher are observation, interviews, and documentation. Data analysis techniques used by the researcher are data reduction, display of data and verification. The researcher uses credibility, transferability, and confirmation in the data validity test. The results of this study indicate that the implementation of entrepreneurial practice runs well and smoothly. The effectiveness of entrepreneurial practices to foster the interest in entrepreneurship works effectively. It is evident that teachers, facilities, and materials are sufficient. The process of entrepreneurship practice successfully fosters entrepreneurship and entrepreneurship skills for students and is able to generate interest in entrepreneurship.